Fabrication of Al2O3-ZrO2 composite catalysts with tunable acid-base properties for highly efficient aldol condensation of furfural with acetone - Liyuan Yuan; Mengran Liu; Shanshan Liu; Guoli Fan; Lan Yang; Feng Li (Catalysis Communications, 2022)
A series of alumina-zirconia composite catalysts were fabricated via a homogeneous two-step solution-phase strategy and employed in the aldol condensation of furfural with acetone to produce furfurylidene acetone (FAc). It was demonstrated that after tuning the surface acid-base properties of Al2O3-ZrO2 composites by varying the Al content, a superior catalytic performance (Al/(Al + Zr) ratio of 0.5) with a FAc yield of larger than 90.0% compared to single metal oxides and other mixed metal oxides reported was obtained.